Corporate governance and development reform, financial systems and legal frameworks - Arun, Thankom; Turner, John.; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar, 2009)
This book analyses the complex relationship between corporate governance and economic development by focusing on the reform of corporate governance, the role of the legal system, and the interconnections with the financial system.
1. Corporate governance and development : reform, financial systems and legal framework - an overview / Thankom Gopinath Arun and John Turner -- ch. 2. Gains and losses of adopting new standards of corporate governance : a CGE analysis of Argentina / Omar O. Chisari and Gustavo Ferro -- ch. 3. The Anglo-American model of corporate governance in sub-Saharan Africa : explanatory and normative dimensions / Royston Gustavson, Nicholas Ndegwa Kimani and Donald Atieno Ouma -- ch. 4. Corporate governance and the transformation of the electricity sector in Britain and Spain : the interaction between national institutions and regulatory choices / Michel Goyer and Rocío Valdivielso del Real -- ch. 5. The relationship between debt structure and firm performance in India / Sumit K. Majumdar and Kunal Sen -- ch. 6. The corporate governance role of capital markets : a Bangladesh perspective / Faizul Haque -- ch. 7. Corporate governance of banks in developing economies : concepts and issues / Thankom Gopinath Arun and John Turner -- ch. 8. Improving corporate governance of banks : issues and experience from Bangladesh / M. Masrur Reaz -- ch. 9. Corporate governance regulation and board decision making during takeovers / Blanaid Clarke -- ch. 10. Shareholder protection : a leximetric approach. / Priya P. Lele and Mathias M. Siems -- ch. 11. Legal aspects of UK bank corporate governance / Dalvinder Singh.
Includes bibliographical references and index.
Keywords: Corporate governance; Corporations -- Finance; Electronic books